7.2k views
4 votes
!!!!SHOW WHY IT IS CORRECT PLEASEEE!!!!
\and please don't steal the points :(

!!!!SHOW WHY IT IS CORRECT PLEASEEE!!!! \and please don't steal the points :(-example-1
User Alex White
by
4.9k points

2 Answers

7 votes
3(2t+d)=6t+3d

you multiply the outside number with everything inside so 3 times 2t = 6t and 3 times d = 3d
User Paul Tsupikoff
by
5.1k points
5 votes

Answer: Its correct because 3(2t+d) = 6t + 3d are equal.

Explanation:

First we need to solve the equation

3( 2t+d ) = 6t + 3d //// Do some distributive property

6t + 3d = 6t + 3d //// Do you see it . . . They are equal to each other.

So its true.

User Shaggydog
by
5.0k points